2019
DOI: 10.1017/s1047951118002329
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular function by echocardiography, tissue Doppler imaging, carotid intima-media thickness, and asymmetric dimethyl arginine levels in obese adolescents with metabolic syndrome

Abstract: PurposeThe aim of our study was to assess left ventricle and right ventricle systolic and diastolic functions in obese adolescents with metabolic syndrome using conventional echocardiography and pulsed-wave tissue Doppler imaging and to investigate carotis intima-media thickness, and asymmetric dimethyl arginine levels.MethodsA total of 198 obese adolescents were enrolled in the study. The obese patients were divided into metabolic syndrome group and non-metabolic syndrome group. All subjects underwent laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…As for glucose and lipid regulation indicators, all metabolic parameters were significantly altered amongst the two groups of participants. This almost comes in complete agreement with the findings from the prospective study by Aslan et al, which demonstrated comparable results regarding plasma glucose, HDL, triglycerides, and cholesterol levels, but not LDL levels [26].…”
Section: Discussionsupporting
confidence: 92%
“…As for glucose and lipid regulation indicators, all metabolic parameters were significantly altered amongst the two groups of participants. This almost comes in complete agreement with the findings from the prospective study by Aslan et al, which demonstrated comparable results regarding plasma glucose, HDL, triglycerides, and cholesterol levels, but not LDL levels [26].…”
Section: Discussionsupporting
confidence: 92%
“…Forty‐three studies eligible for systematic review reported matching LVDF measures to those included in the meta‐analysis (Figure 4). 19–21,26,28,29,33,35,37,39,40,44,46,48–50,52–54,57–59,61–81 A full list of these results is given in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐three studies eligible for systematic review reported matching LVDF measures to those included in the meta‐analysis (Figure 4 ). 19 , 20 , 21 , 26 , 28 , 29 , 33 , 35 , 37 , 39 , 40 , 44 , 46 , 48 , 49 , 50 , 52 , 53 , 54 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 A full list of these results is given in Table S5 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, adjustment for BMI along with CRF attenuated the secular trends to a larger degree than did attenuation by CRF per se for AMI and HF. The contrasting trends for AMI and HF make sense considering the mounting evidence for a stronger link between obesity and cardiac remodelling compared with the link between obesity and AMI in younger people [15,16,39]. Moreover, it is clear that the impacts of some conventional risk factors on the decline are far greater for AMI than for HF [2], such that cholesterol and smoking are less associated with incident HF, whereas BMI [39] or triglycerides [14] are stronger risk factors for HF.…”
Section: Discussionmentioning
confidence: 99%